Modulating the electronic configuration of Co species in MOF/MXene nanosheet derived Co-based mixed spinel oxides for an efficient oxygen evolution reaction. Issue 1 (23rd November 2022) - Xu, Chuming; Yang, Xifeng; Li, Shuang; Li, Keke; Xi, Benjun; Han, Qing-Wen; Wu, Ya-Pan; Wu, Xue-Qian; Chi, Ru-an; Li, Dong-Sheng
Abstract : Mixed Co-based spinel oxides were synthesized via a simple MOF/MXene pyrolysis–reorganization strategy, which revealed that the coupling effect between Co3 O4 and Co2 TiO4 is crucial for improving OER activity. Abstract : The electronic configuration of Co cations at octahedral (Oct) sites plays a crucial role in the catalytic activity of Co3 O4 -based spinel oxides toward the oxygen evolution reaction (OER). However, there are few reports on modulating the electronic configuration of partial CoOct 3+ (t62ge0g) to CoOct 2+ (t62ge1g) for further promoting their OER performances. Herein, a metal–organic framework (MOF)/MXene composite material pyrolysis–reorganization strategy is developed to obtain heterogeneous Co-based mixed spinel oxides, Co3 O4 /Co2 TiO4 . By regulating the pyrolysis temperature, the mesoporous structures and the electronic configuration of CoOct cations of mixed spinel oxides can be simultaneously optimized, leading to exceptional OER performances with low overpotentials of 280 mV on a glassy carbon electrode and 260 mV on Ni foam at 10 mA cm −2 as well as good stability in alkaline solution. The synergistic catalytic effect between CoOct 3+ in Co3 O4 and CoOct 2+ in Co2 TiO4 is shown to be crucial for improving the OER activity. This finding will provide a new pathway for promoting the OER activity of Co-based spinel oxides.